PROFIL GURU SEKOLAH DASAR DALAM MENGAJAR IPA ELEMENTARY SCHOOL TEACHER PROFILE IN TEACHING SCIENCE - Tri Jalmo (Jurnal Pembelajaran Biologi: Kajian Biologi dan Pembelajarannya, 2016)
Abtract: The research was conducted to discribe the profile of the elementary school teacher in the teaching science. Single-series type was used as research method, and the subject selection method was purposive sampling. The subjects are teachers from grade III, IV, and V, with total subject are 17 teachers from 6Â  elementary school in Rajabasa district of Bandar Lampung. Teaching profile data collected through observation and questionnaire. The data were analyzed descriptively and compared with the standard of the education process and the principle of science. The result shows that 83,33% of teachers in the opening lesson still not in accordance with the standard, 72,21% of teachers dominate on core lesson activities, and students only listening and answering teachers questions. Classroom atmosphere is not conducive during the learning process. 61.11% of teachers use teaching tools. Thus it can be concluded that the science learning process in elementary schools in Rajabasa not in accordance with the standards and principles of science. Keys Word: Teacher Profile , Elementary School and Science